2016
DOI: 10.1016/j.pestbp.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Survival, growth, detoxifying and antioxidative responses of earthworms (Eisenia fetida) exposed to soils with industrial DDT contamination

Abstract: The survival, growth, activity of the biotransformation system phase II enzyme glutathione-S-transferase (GST) and the oxidative defense enzyme catalase (CAT) of earthworms exposed to the contaminated soils from a former DDT plant and reference soils were investigated, and compared with the corresponding indicators in simulated soil-earthworm system, unpolluted natural soils with spiked-in DDT series, to identify the toxic effects of DDT on earthworms and their cellular defense system in complex soil system. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…For example, LC 50 for p,p'-DDT is given as >1000 mg/kg, for γ-HCH as 68 mg/kg; and LC 50 for mancozeb, the most toxic of dithiocarbamates, is 299 mg/kg. Limited acute toxicity of p,p'-DDT against E. foetida is also confirmed by Shi et al (2016), who estimated its 14 d median lethal concentration (LC 50 ) to 273.8 mg/kg soil. Thus, it seems that only in sample MLY3 p,p'-DDT might have contributed to the observed mortality.…”
Section: Discussionmentioning
confidence: 80%
“…For example, LC 50 for p,p'-DDT is given as >1000 mg/kg, for γ-HCH as 68 mg/kg; and LC 50 for mancozeb, the most toxic of dithiocarbamates, is 299 mg/kg. Limited acute toxicity of p,p'-DDT against E. foetida is also confirmed by Shi et al (2016), who estimated its 14 d median lethal concentration (LC 50 ) to 273.8 mg/kg soil. Thus, it seems that only in sample MLY3 p,p'-DDT might have contributed to the observed mortality.…”
Section: Discussionmentioning
confidence: 80%
“…The results were evaluated by probit analysis [20,[22][23][24][25] using the Statgraphics Centurion statistical program XVI. The experimental design used was completely randomized, with the worm mortality for LC50 used as the response variable.…”
Section: Discussionmentioning
confidence: 99%
“…All the flasks were subjected to 12/12 h light/dark periods at a temperature of 25-28 • C. Each concentration had four repetitions. The mortality (%) (for LC50) was evaluated at 14 days, without the addition of food [20,21].…”
Section: Artificial Substrate Testmentioning
confidence: 99%
“…According to Wang et al [17], guadipyr showed low toxicity to earthworms and did not elicit an effect on earthworm reproduction or growth in artificial soils at concentrations of 100 mg/kg. Shi et al [18] found that contamination of DDT higher than 200 mg/kg was significantly toxic to both the survival and the growth of earthworms. Miglani and Bisht S.S. [19] concluded that the use of pesticides in agriculture systems results in many ecological problems.…”
Section: Introductionmentioning
confidence: 99%